Exploring the Role of Shared Mobility in Alleviating Private Car Dependence and On-Road Carbon Emissions in the Context of COVID-19 - Zhang, Xiaoyu; Shao, Chunfu; Wang, Bobin; Huang, Shichen; Mi, Xueyu; Zhuang, Yan (Frontiers in Environmental Science, 2022)
Shared mobility is increasingly popular worldwide and travelers show more complex choice preferences in the post-pandemic era. This paper aims to explore the role of shared mobility in the context of COVID-19 by comparing the travel mode choice behavior with and without shared mobility. Considering the shared mobility services of ride-hailing, ride-sharing, car-sharing, and bike-sharing, the stated preference survey is designed and the mixed logit model with panel data is applied. The results show that if shared mobility is absent, approximately 50% of motorized mobility users and 84.62% of bike-sharing adopters switch to using private car and public transport respectively. The perceived pandemic severity positively affects the usage of car-sharing and bike-sharing, while negatively affects the ride-sharing usage. Under different pandemic severity levels, the average probabilities of private car choice with and without shared mobility are 38.70% and 57.77% respectively, thus shared mobility would alleviate the private car dependence in a post-pandemic future. It also helps to decrease the on-road carbon emissions when the pandemic severity is lower than 53. These findings suggest policymakers to maintain the shared mobility ridership and contain the pandemic at the same time. Additionally, pricing discount and safety enhancement are more effective than reducing detour time to protect ride-sharing against COVID-19.